A Simulation Study of the Performance of Parametric Dollar Unit Sampling Statistical Procedures - Menzefricke, Ulrich; Smieliauskas, Wally (Journal of Accounting Research, 1984)
Ulrich Menzefricke, Wally Smieliauskas, A Simulation Study of the Performance of Parametric Dollar Unit Sampling Statistical Procedures, Journal of Accounting Research, Vol. 22, No. 2 (Autumn, 1984), pp. 588-604